Montessori Education: Teacher Perceptions of Challenges in Transitioning to Virtual Instruction - Catherine M. Scott; Brooke Myers (University of Kansas, 2021)
In 2020, Montessori teachers and families across the world had to adjust as schools were closed because of the rapid onset of the COVID-19 pandemic. Those working in the Montessori classroom, which typically favors a hands-on approach and limited use of technology, had to devise new ways to engage with students in the virtuallearning environment. How do teachers perceive that the transition to online learning affected their instruction? This descriptive case study examined the ways in which a school's Lower and Upper Elementary Montessori teachers adjusted their instruction to meet student needs online, as well as the benefits and challenges that the teachers felt they and the students experienced as a result.